2022
DOI: 10.1063/5.0092889
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of horizontal-half-loop arrays and stacking fault expansion behavior in thick SiC epitaxial layers

Abstract: The formation mechanism of half-loop arrays (HLAs) that form parallel (horizontal) to the step-flow direction in 120  μm thick 4H-silicon carbide (SiC) epitaxial layers was investigated using ultraviolet photoluminescence (UVPL) imaging and x-ray topography (XRT). The horizontal-HLAs are generated by the multiplication and glide of basal plane dislocation (BPD) loops that are created within the epitaxial layer. The BPD loops were initiated after ∼40–50  μm of growth from a small BPD segment, which glides towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Despite the commercialization of unipolar 4H-SiC devices in the early 2000s, defects remained a challenge for bipolar and higher voltage (6.5 kV+) devices. 4,5 Other promising WBG semiconductors such as GaN and β-Ga 2 O 3 6−10 also face issues such as reduced breakdown voltage and increased leakage current due to extended defects. 6,7 Examples of extended defects include micropipes, 11 threading dislocations (TD), 12 basal plane dislocations (BPDs), 13 ingrown stacking faults (IGSF), 14 polytype inclusions, 15 and recombination-induced stacking faults (RISF).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the commercialization of unipolar 4H-SiC devices in the early 2000s, defects remained a challenge for bipolar and higher voltage (6.5 kV+) devices. 4,5 Other promising WBG semiconductors such as GaN and β-Ga 2 O 3 6−10 also face issues such as reduced breakdown voltage and increased leakage current due to extended defects. 6,7 Examples of extended defects include micropipes, 11 threading dislocations (TD), 12 basal plane dislocations (BPDs), 13 ingrown stacking faults (IGSF), 14 polytype inclusions, 15 and recombination-induced stacking faults (RISF).…”
mentioning
confidence: 99%
“…Similar formation energies of its many polytypes hampered development via challenges in crystal growth and defect formation. Despite the commercialization of unipolar 4H-SiC devices in the early 2000s, defects remained a challenge for bipolar and higher voltage (6.5 kV+) devices. , Other promising WBG semiconductors such as GaN and β-Ga 2 O 3 also face issues such as reduced breakdown voltage and increased leakage current due to extended defects. , Examples of extended defects include micropipes, threading dislocations (TD), basal plane dislocations (BPDs), in-grown stacking faults (IGSF), polytype inclusions, and recombination-induced stacking faults (RISF) . The impact of these defects on device performance depends on the combination of defect structure, material system, and device type.…”
mentioning
confidence: 99%
“…However, in epitaxial wafers with thick epilayers, the effect of the lattice mismatch extends to the substrate side, generating a considerable stress inside the substrate. Mahadik et al 21 recently reported the formation of BPD loops in a 120 μm thick 4H-SiC epi-wafer. They observed BPDs that were generated by inclusion and propagated beyond the epi/sub interface to the interior of the substrate.…”
mentioning
confidence: 99%